Hubungan antara Orang Hidup dan Meninggal: Kajian Etika Kristen terhadap Ritual Mambere Mangan Nadob Matei - Riski Bartimeus Mart Purba; Fredi Ardo Purba (Program Pascasarjana UKIM, 2024)
The understanding of the relationship between the living and the dead is a problematic issue in Christianity, which generally separates the living and the dead. In contrast, traditional Simalungun beliefs recognize the existence of such a relationship, as seen in the ritual of mambere mangan na dob matei. This practice involves the provision of food for deceased ancestors, based on a deep respect for the ancestors as Naibata Nataridah (visible God), who are believed to bless the lives of their descendants. This study uses the literature study research method by conducting a literature review to analyze the Christian ethics of the ritual. The results show that through the Mambere Mangan Nadob Matei ritual, Simalungun Christians believe in the existence of a relationship between the living and the dead, which is based on respect for parents (ancestors) as Naibata Nataridah (visible God) who can bless the lives of their children.